2020
DOI: 10.1002/med.21765
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the tumor microenvironment for effective immunotherapy

Abstract: Advances in immunotherapy have led to durable and long‐term benefits in a subset of patients across a number of solid tumor types. Understanding of the subsets of patients that respond to immune checkpoint inhibitors at the cellular level, and in the context of their tumor microenvironment (TME) is becoming increasingly important. The TME is composed of a heterogeneous milieu of tumor and immune cells. The immune landscape of the TME can inhibit or promote tumor initiation and progression; thus, a deeper under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
156
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 185 publications
(339 reference statements)
0
156
0
Order By: Relevance
“…Clarifying the mechanisms of tumor immune evasion and immune drug resistance are necessary for improving clinical outcomes for patients. Accumulating evidence has confirmed abnormalities in the tumor microenvironment (TME) were correlated with the efficacy of PD-1/PD-L1 blockade and the angiogenic factors could contribute to the immunosuppression in the TME by inducing vascular abnormalities, suppressing antigen presentation and immune effector cells (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarifying the mechanisms of tumor immune evasion and immune drug resistance are necessary for improving clinical outcomes for patients. Accumulating evidence has confirmed abnormalities in the tumor microenvironment (TME) were correlated with the efficacy of PD-1/PD-L1 blockade and the angiogenic factors could contribute to the immunosuppression in the TME by inducing vascular abnormalities, suppressing antigen presentation and immune effector cells (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high MSI is correlated with a stronger immune response ( 57 ) and patients with high-TMB are more likely to benefit from ICIs ( 58 , 59 ). Infiltration of immune cells and the function of immune cells in the tumor microenvironment serve as prognostic factors in predicting the response ( 29 , 60 ). Recent studies also indicated that the gut microbiome was associated with the efficacy of ICIs ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the complex cell types that make up the TME and how they interact sheds light on malignant primary and secondary lung cancers [45,46]. Treatment failure and resistance in primary and secondary lung tumours have revealed that these cells exhibit extensive inter-and intra-tumoural heterogeneity [42,45].…”
Section: Spatial Profiling Technologies For Lung Cancermentioning
confidence: 99%
“…Treatment failure and resistance in primary and secondary lung tumours have revealed that these cells exhibit extensive inter-and intra-tumoural heterogeneity [42,45]. As a result, understanding the molecular relationship between cell types and their morphological and pathological characteristics is critical [45,46]. Since the late 1990 s, when in-situ sequencing methods to genomic hybridization were developed, the field of spatial biology has grown rapidly, particularly in the last five years [47,48].…”
Section: Spatial Profiling Technologies For Lung Cancermentioning
confidence: 99%
“…Of these cases, long-term benefit to PD-1/PD-L1 immune checkpoint inhibitors (ICIs) are observed in only 20-30%. There is currently an unmet clinical need for predictive biomarkers for ICI therapy 24 . Both membranous tumour cell expression of PD-L1 5 and tumour mutation burden (TMB) 6, 7 are FDA approved companion diagnostic biomarker tests used to stratify patients for immunotherapy, however these appear to be independent variables in their predictive capacity 6, 8, 9 .…”
Section: Introductionmentioning
confidence: 99%